Biblioteca Nacional
Sobre el concurso y la obra para la Biblioteca Nacional de Argentina en Buenos Aires.
Keywords: TESTA, CLORINDO; BULLRICH, FRANCISCO; CAZZANIGA DE BULLRICH, ALICIA; ARGENTINA; BUENOS AIRES (PROV); BUENOS AIRES; CONCURSOS; CONCURSOS NACIONALES; PREMIOS; BIBLIOTECAS; BIBLIOTECAS NACIONALES